The Pattern of Utilizing Local Community Wisdom to Support Tourism in Berastagi - Siregar, Muhammad Ridho; Nuraini, Cut; Azhari, Ihsan (International Journal Papier Advance and Scientific Review, 2023)
Although Berastagi has the allure of night tourism, the city is also known as a culinary center, thanks to the presence of the Pasar Kaget. However, previous research has not extensively addressed the aspects of night tourism and the utilization of local wisdom. This research aims to identify night activities in Berastagi based on the pattern of utilizing local wisdom. The two main theories underlying this research are night tourism and local wisdom. The intended pattern of utilization is a roadmap for how night tourism can be better developed. The theory of night tourism identifies 4 main component patterns: economic, social, environmental, and the night atmosphere. Meanwhile, local wisdom emphasizes the first pattern, which is the value of trust, and the second, which is the cultural life that grows within the community. The research method used is qualitative descriptive, with data obtained through interviews and field observations. The research results show that the Berastagi community has felt the economic impact of night tourism, and integrating Karo culture into night tourism can enhance business opportunities and economic growth. Although there is negative public perception of night tourism, the Karo customary institution in Berastagi plays a role as a local force in safeguarding social aspects during these activities. To enhance night tourism in Berastagi, improvements are needed, such as the concentration of night tourism areas and the incorporation of traditional Karo tribal ornaments. By making Karo culinary and culture the distinctive identity, the city of Berastagi can build a unique night atmosphere, providing a different experience between night and day tourism.